Transient current effects on poly(o-methoxyaniline) films irradiated by pulsed electron beam - Santos, L. F.; Chinaglia, D. L.; Faria, R. M. (Elsevier B.V., 1999)
Fast transient current decay was recorded on POMA samples during current pulses (in the order of milliseconds) provided by a low energy electron beam under an applied field. The characteristic time decay depends on the electron beam energy and on the bias polarity. The results were explained taking into account the effect of space charge, the intrinsic conductivity of the non-irradiated region of the sample and the radiation-induced conductivity of the thin irradiated region. Fitting parameters may provide the value of both intrinsic and radiation-induced conductivities and the average electron range.
Keywords: charge transport measurements; electron beam; conductivity; polyaniline and derivatives